2017
DOI: 10.21776/ub.jiap.2017.003.02.7
|View full text |Cite
|
Sign up to set email alerts
|

Governmental Factors for Household Energy Savings: Adding The Theory of Planned Behavior

Abstract: This study aims to investigate the relationship between household energy savings behaviors and governmental factors by implementing the theory of planned behavior (TPB). This cross-sectional study used a unique dataset compiled by Statistics Indonesia: Village Potential Statistics (VPS) Year 2011 and Environmental Care Behaviour Survey (ECBS) Year 2013. Variables connected to HES were decided by applying a logistic regression model with multivariable. Manual backward stepwise regression was performed. In the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The current study also revealed that households do not agree on waste management practices that take up too much time and waste time. This result is consistent with previous study in Indonesia [7] which discovered that attitude, subjective norm, and perceived behavioral control all are influencing attitude. This shows that having knowledge of solid waste management practice can increase the perceived behavioral control towards intention.…”
Section: Plos Onesupporting
confidence: 93%
See 2 more Smart Citations
“…The current study also revealed that households do not agree on waste management practices that take up too much time and waste time. This result is consistent with previous study in Indonesia [7] which discovered that attitude, subjective norm, and perceived behavioral control all are influencing attitude. This shows that having knowledge of solid waste management practice can increase the perceived behavioral control towards intention.…”
Section: Plos Onesupporting
confidence: 93%
“…In most developing countries, open, unregulated dumps are still the most common means of waste disposal. Many health-related problems result from improper waste management in urban areas [6,7]. Environmental phenomena such as water, soil, and air pollution have been blamed on insufficient solid waste management [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation